2015
DOI: 10.3402/jchimp.v5.29624
|View full text |Cite
|
Sign up to set email alerts
|

When a pulmonary embolism is not a pulmonary embolism: a rare case of primary pulmonary leiomyosarcoma

Abstract: Arterial leiomyosarcomas account for up to 21% of vascular leiomyosarcomas, with 56% of arterial leiomyosarcomas occurring in the pulmonary artery. While isolated cases of primary pulmonary artery leiomyosarcoma document survival up to 36 months after treatment, these uncommon, aggressive tumors are highly lethal, with 1-year survival estimated at 20% from the onset of symptoms. We discuss a rare case of a pulmonary artery leiomyosarcoma that was originally diagnosed as a pulmonary embolism (PE). A 72-year-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…PPLs are extremely rare lesions that typically show an aggressive and often lethal clinical course [ 1 , 2 , 3 , 4 , 5 , 6 ]. In a large population-based study, examining 231 patients with PPL, Qin et al [ 1 ] found the median age at presentation was 65.8 years, with a patient survival time of 14.0 months, with 1, 3, and 5-year survival rates of 52.7%, 29.0%, and 22.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PPLs are extremely rare lesions that typically show an aggressive and often lethal clinical course [ 1 , 2 , 3 , 4 , 5 , 6 ]. In a large population-based study, examining 231 patients with PPL, Qin et al [ 1 ] found the median age at presentation was 65.8 years, with a patient survival time of 14.0 months, with 1, 3, and 5-year survival rates of 52.7%, 29.0%, and 22.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…PPLs present with symptoms similar to other pulmonary neoplasms, including cough, hemoptysis, dyspnea, asthenia, chest and back pain, and weight loss [ 1 , 3 ]. Due to their rarity, PPLs have been misdiagnosed as pulmonary emboli, as other pulmonary neoplasms, or as cardiac neoplasms [ 1 , 3 , 4 , 5 ]. Pulmonary artery leiomyosarcomas have also been misdiagnosed as chronic thromboembolic disease, due presenting with dyspnea, chest pain, and right-sided heart failure [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The case reports are CHF associated with protease inhibitors ( 9 ); Kaposi’s sarcoma of the heart ( 10 ); 2 Takotsubo reports ( 11 , 12 ); GI bleeding secondary to aortic cavitary fistula ( 13 ) in endocarditis with complete heart block; pulmonic valve endocarditis presenting as neck pain ( 14 ); tricuspid valve endocarditis with Mobitz II heart block ( 15 ); primary pulmonary leiomyosarcoma disguised as a pulmonary embolus ( 16 ); aspergillus endophthalmitis ( 17 ); cutaneous tuberculosis ( 18 ); and, finally, a report increasing our awareness of complications of acetaminophen overdose ( 19 ), and a review on GI bleeding and fistulas ( 20 ).…”
mentioning
confidence: 99%